Proposta de modificação da técnica da osteotomia transfibular para o tratamento das fraturas pósterolaterais do planalto tibial - Robinson Esteves Santos Pires (2017)
OBJECTIVE: Propose a modification to the transfibular osteotomy technique for posterolateral fractures of the tibial plateau and evaluate complication rates and preliminary functional outcomes. PATIENTS AND METHOD: From January 2013 to October 2014, 11 patients underwentmodified transfibular osteotomy for posterolateral fractures of the tibial plateau and were subsequently enrolled in the study. All patients were invited to return to the hospital for another clinical and imaging evaluation.Outcome measurements were complications related to the transfibular approach (peroneal nerve palsy; knee instability; loss of reduction; nonunion and malunion of fibular osteotomy) and functional outcomes according to the American Knee Society Score and American KneeSociety Score/Function. RESULTS: Follow-up average was 16 months (12-21±3). Two patients failed to follow up and were excluded from the study. Of the nine remaining patients, none demonstrated evidence ofperoneal nerve palsy. One patient presented loss of reduction and fixation of the fibular neck osteotomy and required screw fixation revision. No fibular osteotomy malunions occurred. One patient presented malunion of the tibial plateau fracture with 10o of varus deformity. No patients demonstrated clinically detectable posterolateral knee instability following surgery. The American Knee Society Score was good in 7 patients (77.8%), fair in 1 (11.1%), and poor in 1 (11.1%). The American Knee Society Score/Function showed 80 points on average (60- 100±11). CONCLUSION: The proposed modification to the original transfibular technique presented low complication rates and satisfactory functional outcomes according to the American Knee Society Score and American Knee Society Score/Function.